Aging Workforce and Workforce Shortages: The Looming Public Crisis - Silva, Diego Barbosa da; Silva, Anna Karolina Barbosa da; Oliveira, Renata Aparecida Rosa de; Forti, Julianne de Oliveira (Brazilian Journal of Implantology and Health Sciences, 2025)
Northern New England dental profession is experiencing a sorrowful and new utility health crisis due to an ageing workforce and incessant lack of new practitioners. This paper presents the interaction of demographic change, workforce distribution, and access to oral health services in Maine, New Hampshire, and Vermont in 2015 to 2025. Secondary data were elicited using a mixed-method, whereby state workforce reports were used to provide data on age trends, rates of retirement and records of the professional associations to determine the ratio of dentists to population. Geographic information systems (GIS) were used to map areas of gap of services, and survey data of dental providers in the region showed barriers to recruitment and retention. Findings indicate that there is a fast aging dental workforce and almost 50 percent of the practitioners are nearing retirement age, and there is a low replacement of younger professionals, particularly in rural communities. Such shortages are associated with the increasing unmet oral health needs and the increasing geographic differences in access to care. The results show that there is an immediate need to create specific policy interventions, including workforce pipeline initiatives, loan-repayment incentives, and the implementation of larger dental team models, to avert the deeper oral health crisis in Northern New England.